ENHANCE A TRACE OF THE ISLAMIC SULTANATE BANTEN, ENFORCEMENT OF MANAGEMENT ISLAMIC - Yuliusman KY; M Iqbal Irham; Sugeng Wianto (Jurnal Ekonomi, 2023)
When mentioning the word Banten, one's image is generally immediately drawn to the presence of Islamic scholars, Islamic warriors and warriors on the island of Java, and is often associated with mystical nuances so that its echoes are heard throughout the world. However, not many people know about the process of the Islamic movement in the land of scholars and warriors. This article, which carries the title Traces of the Islamic Sultanate of Banten, the Conquest of Sunda Kelapa and the Spread of Religion, explores the role of Prabu Siliwangi's grandson named Syarif Hidayatulloh bin Maulana Syarif Abdullah Khan, one of the Wali Songo with the title Sunan Gunung Jati and his son Maulana Hasanuddin in struggling to spread the teachings of Islam as well as bringing change from Hindu-Buddhist to Islamic Civilization which teaches the essence of life according to the guidance of the Prophet Muhammad.